Balancing the European Monetary Union - an Impact Analysis on the Return of National Currencies - Anke Mönnig (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2012)
The current state budget crisis in the EU and the numerous futile efforts to solve the problem has brought back the fraction of people that argument in favour of an exit strategy of Germany from the European monetary union (EMU) or even the break-up of the EMU in total. This paper investigates for the case of Germany, whether or not a return to a new deutsche mark would be beneficial. It applies the macro-econometric input-output model INFORGE for this analysis, as it is able to quantify direct and indirect effects on inter-industrial level as well as on the demand and supply sides of the economy. Above that, INFORGE considers sectoral effects which are extremely important for the evaluation of this impact analysis. The quantitative results of the computed projection shows, that a return to a national currency would lower Germany's growth path mainly due to the expected appreciation of the new currency. A second scenario, which assumes a worsening of the crisis within the remaining EMU would intensify the negative implications for Germany. Although the results should be considered with respect to their strong assumptions, consensuses among economists exist that these assumptions might be initiated in case of an EMU break-up. Hence, in the case of Germany, the effort of doing everything to foster the future existing of the monetary union is of utmost importance.
Keywords: E2; E5; F4; 330; European Monetary Union; projection; impact analysis